The Influence of Entrepreneurial Knowledge and Implementation of Business Center Activities on the Entrepreneurial Interest of Grade XI Students of the Marketing Department of SMK NEGERI 1 MEDAN - Hutapea, Dolse Maria; Agusti, Ivo Selvia (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of entrepreneurial knowledge and the implementation of business centre activities on the entrepreneurial interest of eleventh-grade marketing students at SMK Negeri 1 Medan. A quantitative approach with an ex post facto design was employed, involving 63 respondents selected through total sampling. Data were collected using multiple-choice tests and questionnaires, then analyzed using multiple linear regression. The results show that: (1) Entrepreneurial knowledge and business centre activities simultaneously have a positive and significant influence on entrepreneurial interest (F = 30.790; sig = 0.001); (2) Entrepreneurial knowledge has a significant partial effect on entrepreneurial interest (t = 2.737; sig = 0.008); (3) Business centre activities also have a significant influence on entrepreneurial interest (t = 2.563; sig = 0.013). The coefficient of determination (R²) indicates that these variables contribute 50.6% to entrepreneurial interest. These findings highlight the importance of integrating entrepreneurial education with hands-on practice through school business centres to enhance students’ readiness to become young entrepreneurs.